Artists and Multiple Job Holding—Breadwinning Work as Mediating Between Bohemian and Entrepreneurial Identities and Behavior - Lindström, Sofia (Nordic Journal of Working Life Studies, 2016)
Artists are known to manage low income and work insecurity by holding multiple jobs. Through an analysis of interview data, this study explores the narratives of 20 visual artists in Sweden regarding breadwinning work. Positive and negative experiences of such work are analyzed in relation to the artists’ work behavior and identity as either ‘bohemian’ or ‘entrepreneurial.’ Breadwinning work may be seen by artists as either enabling autonomy from the market or hindering the construction of a professional identity, depending on these behaviors/identities. However, conditions such as low wage, temporary contracts, and low control over work hours ultimately decides artist’s experiences of breadwinning work. This article adds to the existing knowledge on artistic labour markets by highlighting the role of multiple job holding in mediating between an understanding of the bohemian art for art’s sake artist role and the entrepreneurial role of the artist. NB: The endnotes 7 and 8 have switched places, where endnote 7 should belong to the text of endnote 8 and vice versa